A Hamiltonian Model for Interacting Dipolar Molecules Inside Optical Cavities: Structure, Dynamics and Analysis of Linear and Nonlinear 2D Spectra (2025)
In this work, wepresent atheoretical and computational study of the spectral structure and dynamics of molecular polaritons under linear and nonlinear spectroscopy protocols, such as two-dimensional spectroscopy, with particular emphasis on the system’s response to variations in the dipole-dipole interaction strength between molecules. The system under study consists of an ensemble of dipolar molecular emitters strongly coupled to quantized radiation mode inside an optical cavity. The interaction in this setting gives rise to hybrid light-matter eigenstates known as polaritons. Dissipative processes in the system, such as photon losses and molecular relaxation mechanisms, are introduced through the formalism of open quantum systems by means of Lindbladian and Markovian Bloch-Redfield-Wangsness superoperators. [Tomado de la introducción]